Risk of osteoporosis in patients treated with direct oral anticoagulants vs. warfarin: an analysis of observational studies - Liu, Yumeng; Xie, Xiaoping; Bi, Songqi; Zhang, Qiong; Song, Qingxu; Sun, Yang; Yu, Tiecheng (Frontiers in Endocrinology, 2023)
Aims: evidence on the association between the risk of new-onset osteoporosis and oral anticoagulants remains controversial. We aimed to compare the risk of osteoporosis between direct oral anticoagulant (DOAC) and warfarin use.Methods: studies published up to March 15, 2023 that investigated the association between the use of DOAC and warfarin with the incidence of osteoporosis were identified by online searches in PubMed, EMBASE, the Cochrane Library, and Web of Science performed by two independent investigators. Random or fixed effect models were employed to synthesize hazard ratios (HRs) /relative ratios (RRs) with 95% confidence intervals (CIs) for estimating the risk of osteoporosis correlated with DOAC and warfarin prescriptions. (PROSPERO No. CRD42023401199) Results: our meta-analysis ultimately included four studies involving 74,338 patients.The results suggested that DOAC use was associated with a significantly lower incidence of new-onset osteoporosis than warfarin use (pooled HR: 0.71, 95% CI: 0.57-0.88, P < 0.001, I 2 : 85.1%). Subanalyses revealed that rivaroxaban exhibited a lower risk of osteoporosis compared to warfarin and dabigatran, respectively. Additionally, DOAC revealed a lower risk of developing osteoporosis than warfarin in both male and female patients, in patients with atrial fibrillation (AF), and in patients with the duration of therapy > 365 days.with warfarin users. This study may give us insight into safe anticoagulation strategies for patients at high risk of developing osteoporosis.